Covid-19 vaccination with RST Dr. Soedjono Magelang - Luk Luk Atul Hidayati; Agung Setyabudi; Diana Sri Kurniawati; Septiana Isca Sari; Firman Dwi Cahyo; Naura Nazihah (Community Empowerment, 2022)
To stop the spread of Covid-19 in the Magelang City region, the vaccination raid action was conducted with RST Dr. Soejdono Magelang. This activity begins in September and runs through December 2021. In the Magelang region, vaccination campaigns aimed at the general public are conducted all around the city. Additionally, RST. Dr. Soedjono delivered a vaccine holder to the hospital with a group of Unimma volunteers. The purpose of this vaccination campaign is to stop Covid-19 from spreading and to spread vaccination against it throughout the Magelang Regency. Data entry, vaccine injection, and vaccination card printing are the tasks completed. The results of this vaccination activity are expected to be able to break the chain of the spread of COVID-19 and facilitate services to the public in getting vaccines.